2012
DOI: 10.5402/2012/685852
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis: Reprogramming and the Fate of Mature Cells

Abstract: Apoptosis is essential for embryogenesis, organ metamorphosis, and tissue homeostasis. In embryonic stem cells, self-renewal is balanced with proliferative potential, inhibition of differentiation, and prevention of senescence and apoptosis. Growing evidence supports the role of apoptosis in self-renewal, differentiation of pluripotent stem cells, and dedifferentiation (reprogramming) of somatic cells. In this paper we discuss the multiple roles of apoptosis in embryonic stem cells (ESCs) and reprogramming of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…The increasing of ROS inhibited the survival of reprogramming cells which led to DNA damages, cellular senescence and apoptosis [7]. Thus, the factor which regulates ROS homeostasis may play a critical role for efficient reprogramming [7]. We showed that ROS production is higher in Jdp2 KO MEFs than in WT MEFs and that addition of an oxidative stress inducing reagent increased ROS production in Jdp2 KO MEFs compared with WT KO MEFs (Figure 1).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The increasing of ROS inhibited the survival of reprogramming cells which led to DNA damages, cellular senescence and apoptosis [7]. Thus, the factor which regulates ROS homeostasis may play a critical role for efficient reprogramming [7]. We showed that ROS production is higher in Jdp2 KO MEFs than in WT MEFs and that addition of an oxidative stress inducing reagent increased ROS production in Jdp2 KO MEFs compared with WT KO MEFs (Figure 1).…”
Section: Discussionmentioning
confidence: 94%
“…During reprogramming, Yamanaka factors induced the chromatin changes to generate the stress response including ROS production [50]. The increasing of ROS inhibited the survival of reprogramming cells which led to DNA damages, cellular senescence and apoptosis [7]. Thus, the factor which regulates ROS homeostasis may play a critical role for efficient reprogramming [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is a tightly controlled mode of cell death that eliminates harmful cells upon treatment with anti-cancer drugs. It is morphologically characterized by chromatin condensation, cellular shrinkage, plasma membrane blebbing and nuclear fragmentation (Cheung et al, 2012;Pulido and Parrish, 2003). During apoptosis, a group of cysteine proteases, caspases, which contain a nucleophilic cysteine residue are activated and specifically cleave their substrate proteins after aspartic acid (Strasser et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…(Cheung et al, 2012). In physiology, it plays a crucial role particularly during embryogenesis and metamorphosis.…”
Section: Introductionmentioning
confidence: 99%